2014
DOI: 10.1145/2629531
|View full text |Cite
|
Sign up to set email alerts
|

Content-Based Video Copy Detection Benchmarking at TRECVID

Abstract: This paper presents an overview of the video copy detection benchmark which was run over a period of 4 years (2008)(2009)(2010)(2011) as part of the TREC Video Retrieval (TRECVID) workshop series. The main contributions of the paper include i) an examination of the evolving design of the evaluation framework and its components (system tasks, data, measures); ii) a high-level overview of results and best-performing approaches; and iii) a discussion of lessons learned over the four years. The content-based copy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
3

Year Published

2015
2015
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(11 citation statements)
references
References 27 publications
0
8
0
3
Order By: Relevance
“…In watermarking-based steganography technique [21], a piece of same mark information is imbedded into multimedia content, then the watermarked multimedia content is distributed to users with multicast technology [15]. The watermark information can be copyright information, which can authenticate the owner of the multimedia content.…”
Section: Figure 4 Watermarking Scheme For Multimedia Content Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…In watermarking-based steganography technique [21], a piece of same mark information is imbedded into multimedia content, then the watermarked multimedia content is distributed to users with multicast technology [15]. The watermark information can be copyright information, which can authenticate the owner of the multimedia content.…”
Section: Figure 4 Watermarking Scheme For Multimedia Content Protectionmentioning
confidence: 99%
“…The copy detection framework is shown in Figure (7). The detection method is based on CBCD (Content Based Copy Detection) [21]. An original feature which is registered in feature database through extracting a feature vector representing the original multimedia content.…”
Section: Figure 7 Copy Detection For Copyright Authenticationmentioning
confidence: 99%
“…The report of those competitions concludes that current state-of-the-art methods, which are robustness focused, are not suitable for real-time applications due to their high computational cost [33]. They also reported that current methods are not focused on applications where false alarms (NOFA apps) are not tolerated nor focused on generating compact fingerprints for improving their search in databases [14, 33–35]. Also those methods, which present near perfect scores under simulated attacks in TRECVID competition, present a low performance under non-simulated or real partial-video copies (VCDB benchmark) [10].…”
Section: Related Workmentioning
confidence: 99%
“…Önerilen yöntem, içerik tabanlı kopya bulma probleminde yaygın olarak kullanılan TRECVID 2009 veriseti ile test edilmiştir [10]. Kullanılan test seti ve alınan sonuçlar sırasıyla Bölüm IV-A ve Bölüm IV-B'de detaylı birşekilde açıklanmıştır.…”
Section: Deneylerunclassified
“…Bu çalışmada, test seti olarak TRECVID 2009 veriseti içerisinde tanımlı olan içerik tabanlı video kopya bulma veriseti (CBCD) kullanılmıştır [10]. TRECVID 2009 CBCD veriseti 7 farklı görsel dönüşüm problemini içermektedir.…”
Section: A Test Seti Ve Ataklarunclassified